Depression, sexuality and fibromyalgia syndrome: clinical findings and correlation to hematological parameters - Alves, Bruna; Zakka, Telma M; Teixeira, Manoel J.; Kaziyama, Helena H.; Siqueira, Jose T. T.; Siqueira, Silvia R. D. T. (Arquivos de Neuro-Psiquiatria, 2016)
Fibromyalgia (FM) is characterized by chronic pain and comorbidities. Objective To investigate sexuality and depression in women with FM compared with controls and to correlate the findings with hematological parameters.Methods 33 women with FM and 19 healthy women were included and evaluated with the following instruments: Female Sexual Function Index, Beck Inventory, Visual Analogue Scale, medical history and laboratory exams.Results The prevalence of sexual dysfunction (P = 0.007) and depression (P < 0.001) were higher in the study group than in the control group; they were positively correlated (P = 0.023). The study group showed lower serum concentrations of testosterone, free T4, antinuclear factor, and lower blood hemoglobin and hematocrit.Conclusions FM was associated with high scores of sexual dysfunction and depression, and there were correlations with hematological parameters. We suggest the involvement of immune-inflammatory mediators and FM, which need further investigation to understand their role in FM syndrome and its comorbidities.
Keywords: fibromyalgia; depression; sexuality; hematologic tests